Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let us start by analyzing System A:
[tex]\[ \begin{array}{c} 5x - y = -11 \quad \text{(1)} \\ 3x - 2y = -8 \quad \text{(2)} \end{array} \][/tex]
We were instructed to obtain system B by replacing the second equation by adding it to the first equation multiplied by -2. Let's follow these steps:
1. Multiply equation (1) by -2:
[tex]\[ -2 \times (5x - y) = -2 \times (-11) \][/tex]
[tex]\[ -10x + 2y = 22 \quad \text{(3)} \][/tex]
2. Add equation (3) to equation (2):
[tex]\[ (3x - 2y) + (-10x + 2y) = -8 + 22 \][/tex]
[tex]\[ 3x - 10x = -8 + 22 \][/tex]
[tex]\[ -7x = 14 \quad \text{(4)} \][/tex]
Thus, System B is:
[tex]\[ \begin{array}{c} 5x - y = -11 \\ -7x = 14 \end{array} \][/tex]
Now, let's verify if the solution [tex]\((-2, 1)\)[/tex] is valid for both systems.
For the first equation in System A and System B:
[tex]\[ 5(-2) - 1 = -10 - 1 = -11 \][/tex]
The left-hand side equals the right-hand side, so this solution satisfies the first equation.
For the second equation in System A:
[tex]\[ 3(-2) - 2(1) = -6 - 2 = -8 \][/tex]
The left-hand side equals the right-hand side, so this solution satisfies the second equation of System A.
For the second equation in System B:
[tex]\[ -7(-2) = 14 \][/tex]
The left-hand side equals the right-hand side, so this solution satisfies the second equation of System B as well.
Hence, the solution [tex]\((-2, 1)\)[/tex] is valid for both Systems A and B. Therefore, the correct answer is:
D. The second equation in system B is [tex]\(-7x = 14\)[/tex]. The solution to system B will be the same as the solution to system A.
[tex]\[ \begin{array}{c} 5x - y = -11 \quad \text{(1)} \\ 3x - 2y = -8 \quad \text{(2)} \end{array} \][/tex]
We were instructed to obtain system B by replacing the second equation by adding it to the first equation multiplied by -2. Let's follow these steps:
1. Multiply equation (1) by -2:
[tex]\[ -2 \times (5x - y) = -2 \times (-11) \][/tex]
[tex]\[ -10x + 2y = 22 \quad \text{(3)} \][/tex]
2. Add equation (3) to equation (2):
[tex]\[ (3x - 2y) + (-10x + 2y) = -8 + 22 \][/tex]
[tex]\[ 3x - 10x = -8 + 22 \][/tex]
[tex]\[ -7x = 14 \quad \text{(4)} \][/tex]
Thus, System B is:
[tex]\[ \begin{array}{c} 5x - y = -11 \\ -7x = 14 \end{array} \][/tex]
Now, let's verify if the solution [tex]\((-2, 1)\)[/tex] is valid for both systems.
For the first equation in System A and System B:
[tex]\[ 5(-2) - 1 = -10 - 1 = -11 \][/tex]
The left-hand side equals the right-hand side, so this solution satisfies the first equation.
For the second equation in System A:
[tex]\[ 3(-2) - 2(1) = -6 - 2 = -8 \][/tex]
The left-hand side equals the right-hand side, so this solution satisfies the second equation of System A.
For the second equation in System B:
[tex]\[ -7(-2) = 14 \][/tex]
The left-hand side equals the right-hand side, so this solution satisfies the second equation of System B as well.
Hence, the solution [tex]\((-2, 1)\)[/tex] is valid for both Systems A and B. Therefore, the correct answer is:
D. The second equation in system B is [tex]\(-7x = 14\)[/tex]. The solution to system B will be the same as the solution to system A.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.